Some general considerations about an "ideal" ceramic reinforcement for structural discontinously reinforced AIMC composites prepared by liquid metal routes - Kevorkijan, Varužan (Kovine zlitine tehnologije, 1997)
In this paper an overview of the current understanding of mechanical properties of discontinuously reinforced metal matrix compoties (DR MMCs) is presented and the "ideal" ceramic reinforcement for light metal composites based on Al alloys is identified. Three main problems which must be solved to facilitate the expanding application of DR MMCs with light alloys matrix metals are: (i) superior cost performances - in Al based DR MMCs the quality/cost ratio should be above one, (ii) Active implementation of environmental concerns- DR MMCs should be easy recyclabe, and (iii) the improved ductility - the ductility of the composite should follow the ductility of unreinforced matrix. It is almost postulated that market competitive DR MMCs should be defect free castable and re-castable. It seams that only in this way the most inexpensive processes for production of final components could be developed. Referring to this, the cost effective preparation of molten metal dispersion with at least 20 vol% of fine (less than 10 ?$\mum$?) ceramic paricles produced in situ or directly introduced into a melt becomes the key technological request. In this paper, several new preparation routes for DR MMCs based on chemically improved wetting behaviour of ceramic dispersoids in molten aluminium alloys and chemically activated stabilisation of dispesoids in melt have been discussed. The intrinisic methods and some new market opportunities for DR MMCs have been also presented. Finally, a further selling of the concept of MMCs based on the improvement of the price/quality ration and the important automotive market pull for the improved properties of DR MMCs were introduced.
Keywords: ceramic; keramika; mehanske lastnosti; kvaliteta; cene; kompoziti; aluminij; aluminum; livarstvo